Analisis Peluang Bisnis Dari Hobi Menjadi Sumber Pendapatan - Zebua, Julianus; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
The current dynamic development of the business world allows individuals to transform hobbies into profitable sources of income. This study aims to analyze the potential of various types of hobbies as business opportunities, identify the challenges faced, and formulate development strategies. Using a descriptive qualitative method through a literature study, this research explores how hobbies can transform into sustainable businesses. The results show that hobbies in the fields of creativity, technology, and sports have great market potential, especially supported by digital marketing access. However, the main challenges include fear of failure, social stigma, and limited business management knowledge. Optimal strategies for turning a hobby into a business include conducting market research, starting small, utilizing digital platforms, and developing a systematic business plan. This study concludes that integrating personal interest with professional business principles not only generates financial profit but also provides personal satisfaction and higher productivity.